THE EFFECT OF WORK ENVIRONMENT, ORGANIZATIONAL COMMITMENT AND INCENTIVES ON THE PERFORMANCE OF THE STATE CIVIL APPARATUS THROUGH THE QUALITY OF PUBLIC SERVICES AS AN INTERVENING VARIABLE IN THE OFFICE OF THE REGIONAL REGIONAL AGENCY OF RIAU ISLANDS - Habibi, Habibi; Ngaliman, Ngaliman; Gita Indrawan, Mohammad; Khaddafi, Muammar; Wibisono, Chablullah (CV. Radja Publika, 2022)
This research was conducted to determine the influence, work environment, organizational commitment and state civil apparatus incentives on performance through the quality of public service. The research method used is descriptive quantitative, namely providing an explanation of the work environment description, organizational commitment and incentives of state civil servants on performance through the quality of public services. The sampling technique used in this study is the census sample method, namely the technique of determining the sample when all members of the population are used as samples. Because the total population in the study was 183 people, the entire population was also used as the research sample. The data collection technique in this study used an online questionnaire as a data collection technique designed based on previous literature and research which will be distributed to all ASNs in the Riau Islands Regional Revenue Agency Office. The instrument is calibrated using item validity and reliability coefficient. Validity was tested using SEM-PLS analysis with the help of SmartPLS software. Based on the research results, there are ten conclusions that are relevant to the problems studied in this study.